Pengaruh Kedekatan Orang Tua dengan Anak terhadap Akhlah di Jorong Ranah Sungai Dareh - Chindy Anugrah; Wedra Aprison; Iswantir M; Hamdi Abdul Karim (STIKes Ibnu Sina Ajibarang, 2023)
Children who experience difficulties in their relationships with their parents are a major driving force behind this line of research. These incidents occur because adults lack the knowledge or interpersonal skills to properly care for and raise their children, resulting in the children becoming victims. As a result, adults constantly shun their children, only to eventually come to terms with the fact that their children's current behavior is the result of their own past choices. In this thesis, a quantitative correlation analysis was conducted in a section of the Sungai Dare River. The sample population for this study was calculated using a total sampling method, and there were a total of 65 respondents. Data for this study was collected using a kuesioner, and then analyzed with a straightforward linear regression test. Based on the research conducted, it was found that parental proximity significantly affects children's akhlak; this was demonstrated by the findings of a significant p-value for parental proximity of 0,000 < 0,05 and a t-value for parental proximity of 12,645 > t-table.